Delayed postoperative complications in 624 consecutive cochlear implantation cases. (1st July 2021) - Shi, Lusen; Zhu, Guangjie; Ma, Dengbin; Zhu, Chengwen; Chen, Jie; Qian, Xiaoyun; Gao, Xia
Abstract: Background: Sensorineural hearing loss can be cured by cochlear implantation (CI), but complications can occur. Based on when the complications develop, they are categorized as intraoperative complications, early postoperative complications, or delayed postoperative complications (>3 months after the surgery). Aims/objectives: We aimed to investigate the occurrence of delayed complications after CI surgery, and identify appropriate management methods. Material and methods: We analyzed 624 sensorineural hearing loss patients who had been consecutively treated with CI using the conventional surgical technique in our institution and had been followed-up until September 2017. Results: A total of 43 (6.86%) patients out of the 624 CIs (627 ears) reported complications, and 9 (1.44%) were major complications and 34 (5.42%) were minor complications. Wound infection and device failure were the most common major complications, and hematoma was the most common minor complication. Conclusions and significance: CI surgery is a relatively mature technology; the incidence of complications is low, and with early diagnosis and treatment most complications have a good prognosis. Head trauma was the main reason for children's complications, and patients and guardians should be given good education preoperatively about how to manage the CI postoperatively.